2018
DOI: 10.1016/j.cell.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Translocon Declogger Ste24 Protects against IAPP Oligomer-Induced Proteotoxicity

Abstract: Summary Aggregates of human islet amyloid polypeptide (IAPP) in the pancreas of patients with type-2 diabetes (T2D) are thought to contribute to β-cell dysfunction and death. To understand how IAPP harms cells and how this might be overcome, we created a yeast model of IAPP toxicity. Ste24, an evolutionarily conserved protease that was recently reported to degrade peptides stuck within the translocon between the cytoplasm and the endoplasmic reticulum, was the strongest suppressor of IAPP toxicity. By testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 58 publications
1
58
1
Order By: Relevance
“…The ZMP Core and Accessory modules are capped by a membrane‐spanning α‐barrel module, so named because of our current lack of understanding of its functional role. In light of the ever‐growing literature of Ste24 family orthologs and emergent clinically relevant roles of HsSte24, the Tripartite Architecture will aid in the interpretation of disparate functional data. Furthermore, our proposed Tripartite Architecture can act as a platform to design experiments to better understand both the functional overlap and individual uniqueness of Ste24 family enzymes among different family orthologs (eg, fungal/mammalian/plant/protist).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ZMP Core and Accessory modules are capped by a membrane‐spanning α‐barrel module, so named because of our current lack of understanding of its functional role. In light of the ever‐growing literature of Ste24 family orthologs and emergent clinically relevant roles of HsSte24, the Tripartite Architecture will aid in the interpretation of disparate functional data. Furthermore, our proposed Tripartite Architecture can act as a platform to design experiments to better understand both the functional overlap and individual uniqueness of Ste24 family enzymes among different family orthologs (eg, fungal/mammalian/plant/protist).…”
Section: Resultsmentioning
confidence: 99%
“…Trp97 is located in the α1‐helix and rests at the center of an interfacial, hydrophobic pocket formed from residues of TM α‐helices III and VII, and Phe340 of helix α4. Although functions of absolutely conserved residues “distal” to the Ste24 active site are currently unknown, recent studies implicating HsSte24 as a “translocon unclogger” indicate the presence of functional “hot spots” far from the active site . Roles for absolutely conserved residues of the α‐barrel module in essential “nonenzymatic” functions may also exist; these could include residues essential for biogenesis or protein stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus constructed a structural model of HtpX using the robetta program (Fig. ), based on the crystal structure of the CAAX protease, ZMPSTE24 , a human homolog of HtpX that is also involved in protein quality control in ER in addition to the CAAX cleavage, and mapped the mutation sites . The core domain that contains the protease active site of this model shares several structural features, such as relative arrangement of secondary structures and the predicted active site residues, with those of the other M48 proteases .…”
Section: Discussionmentioning
confidence: 99%
“…This first report of Ste24 as translocon unclogger utilized a "clogging" chimera comprising bacterial and yeast protein domains. A 2018 publication, from a different research group, identified Ste24 as having a similar function against human islet amyloid polypeptide [45], which commonly misfolds in patients with type 2 diabetes (with this "oligomer-induced proteotoxicity" inducing βcell failure). These results, collectively, suggest a role for Ste24 in the ER-associated degradation pathway [46].…”
Section: Translocon Unclogging and Diabetesmentioning
confidence: 99%